Systemic Arterial Hypertension in the Emergency Service: medication adherence and understanding of this disease - Cássia Regina Vancini-Campanharo; Gabriella Novelli Oliveira; Thaisa Fernanda Landim Andrade; Meiry Fernanda Pinto Okuno; Maria Carolina Barbosa Teixeira Lopes; Ruth Ester Assayag Batista (Universidade de São Paulo, 2015)
Objective: to identify the epidemiological profile of hypertension patients, how much they understand about the disease and the rate of adherence to treatment by these patients who had been hospitalized in the Brazilian emergency service. Methods: this cross-sectional study was performed with 116 patients, both male and female and aged over 18 years, who had been hospitalized in the Emergency Service of a University Hospital between March and June, 2013. The studied variables were data referring to socio-demographics, comorbidities, physical activity and knowledge regarding the disease. Patient adherence to treatment and the identification of the barriers were respectively evaluated using the Morisky test and the Brief Medication Questionnaire. Results: most of the patients involved in this study were women (55%), with white skin color (55%), married (51%), retirees or pensioners (64%) and with a low educational level (58%). Adherence to treatment, in most cases (55%), was moderate and the most prevalent adherence barrier was recall (67%). When medication was acquired at no cost to the patient, there was greater adherence to treatment. Conclusion: this study's patients had a moderate understanding about the disease. The high correlation between the number of drugs used and the recall barrier suggests that monotherapy is an option that can facilitate treatment adherence and reduce how often the patients forget to take their medication.